Effect of Surface Composition on Electrochemical Oxidation Reaction of Carbon Monoxide and Ethanol of PtxRh1−x Solid Solution Electrodes - Nguyen Trung Kien; Haruki Yara; Masanobu Chiku; Eiji Higuchi; Hiroshi Inoue (International Journal of Electrochemistry)
PtxRh1−x (x = 0.76, 0.54, and 0.27) solid solutions were prepared by arc-melting. For these solid solutions, the lattice constant was linearly related to the Pt content. The surface compositions of the solid solutions determined by X-ray photoelectron spectroscopy were quite similar to their bulk compositions estimated by energy dispersive X-ray spectroscopy. The CO-stripping voltammograms demonstrated that the onset potential of CO oxidation current density (Eonset) shifted negatively as the surface Pt content decreased, suggesting an increased CO-poisoning resistance. Linear sweep voltammograms of the solid solution electrodes in an Ar-saturated (1 M ethanol + 0.1 M HClO4) solution exhibited that the onset potentials of ethanol oxidation reaction (EOR) current for all solid solution electrodes were lower than of a Pt electrode, and Pt0.54Rh0.46 gave the highest specific activity (SA) of 312 μA·cm−2, which was about 1.8 and 2.5 times higher than the SAs of Pt and Rh, respectively. In situ infrared reflection-absorption spectra exhibited that the Pt0.54Rh0.46 electrode had the bands due to the linear-bonded CO on Pt and bridge-bonded CO on Rh as EOR intermediates around 0.2 V vs. the reversible hydrogen electrode, but the band due to the linear-bonded CO on Rh was not observed even at 0.6 V, suggesting that the existence of the adjacent Pt-Rh sites and the preferential formation of bridge-bonded CO on Rh accelerated the C-C bond cleavage and improved the EOR activity.